Shallow Gamification: Testing Psychological Effects of Framing an Activity as a Game. (May 2015) - Lieberoth, Andreas
This article experimentally dissociates the psychological impact of framing versus game mechanics, when presenting a serious activity as a game. Studies of game elements in nongame contexts tend to describe full packages, with no way of assessing their individual psychological and functional impact. To isolate the effects of framing, students ( N = 90) were assigned to either discuss study environment issues through a list of questions, via a competitive discussion board game, or though the same game artifacts but with no game mechanics. Task engagement and self-reported intrinsic motivation were compared between groups. Results demonstrate that the effects of simply framing the activity as a game though vernacular and artifacts holds almost as much psychological power as the full game mechanics. In both game conditions, interest and enjoyment were significantly superior to controls, but other intrinsic motivation variables remained unchanged. Implications for game design in nongame contexts are discussed, and a framework for differentiating "deep and shallow gamification" in terms of mechanics and framing is developed.